PALAEOMAGNETIC INSIGHTS INTO THE EVOLUTION OF NEOTETHYAN OCEANIC CRUST IN THE EASTERN MEDITERRANEAN - Morris A.; Anderson M.W.; Inwood J.; Robertson A.H.F. (My University, 2006)
A synopsis of palaeomagnetic data from three Late Cretaceous eastern Mediterranean Tethyan ophiolites (Troodos, Hatay and Baër-Bassit) and their sedimentary cover sequences is presented. These data provide valuable insights into the role of regional- and local-scale tectonic rotations in the geodynamic evolution of Neotethyan oceanic crust. The geologically earliest phases of tectonic rotation are documented in the Troodos ophiolite, where rotations around both subvertical and subhorizontal axes are readily related to the development of the spreading fabrics and structures during crustal genesis. Subsequent c. 74° anticlockwise intra-oceanic rotation of a 'Troodos microplate' has been quantified through analysis of the in situ sedimentary cover of the Troodos ophiolite. Results indicate that bulk anticlockwise rotation began soon after the cessation of spreading and ended by the end of the Eocene, with c. 50-60° of microplate rotation being over by the Maastrichtian, the time at which ophiolite thrust sheets were emplaced onto the Arabian continental margin to the east of Troodos. Recent results from the emplaced, structurally dismembered Baër-Bassit ophiolite indicate extreme anticlockwise rotations of ophiolitic thrust sheets varying on a kilometre scale. New data from the post-emplacement sedimentary cover confirm that only a small component of these rotations is due to post-emplacement tectonism. Baër-Bassit represents the leading edge of the emplaced ophiolitic sheet. New data from the more coherent section preserved in the Hatay ophiolite to the north demonstrate significant anticlockwise rotation. This is equivalent to the rotation of the most northerly part of the Baër-Bassit units to the south, and is of the same sense and magnitude as the pre-Maastrichtian phase of microplate rotation documented in the Troodos. This suggests a common, intra-oceanic origin for the majority of the Troodos and Hatay rotations, and a significant component of the more variable rotations observed in Baër-Bassit. Overall, therefore, the data support a model involving: (1) intra-oceanic rotation of a coherent region of crust within the southern Neotethyan basin; this rotated unit is more areally extensive than has previously been inferred from consideration of data from the Troodos ophiolite alone; (2) emplacement of part of the rotated unit onto the Arabian platform; (3) subsequent localized post-emplacement modification, related to the development of the current plate configuration. © The Geological Society of London 2006.
Keywords: Eocene; Maastrichtian; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Mesozoic::Cretaceous::Upper::Maastrichtian; Мезозой::Меловая::Верхний::Маастрихтский